Web-Based Futsal Field Reservation Application at Futsal NR Prabumulih - Farras Zain; Fajriyah Fajriyah; Nurmayanti Nurmayanti3 (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The development of digital technology encourages the sports sector to improve services. Futsal NR Prabumulih still uses a manual booking system that is less practical, especially in terms of time and access. This study aims to design a web-based futsal field booking application to make it easier for users to view schedules, book futsal fields, and make payments online. With a user-friendly interface, this application allows customers to make reservations at any time. In designing this system, UML (Unified Modeling Language) modeling tools such as use case diagrams, activity diagrams, and class diagrams are used to explain system functions, activity flows, and data structures. The system development method used is Rapid Application Development (RAD), which emphasizes the speed of development through iterative prototyping and active user involvement in every stage of development. Testing of the system shows an increase in efficiency in booking management and an increase in customer satisfaction. This application is expected to support modern and integrated services at Futsal NR Prabumulih.